2022
DOI: 10.3389/fonc.2022.850767
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of CSF-1R Predicts Poor Prognosis and CSF-1Rhigh Tumor-Associated Macrophages Inhibit Anti-Tumor Immunity in Colon Adenocarcinoma

Abstract: BackgroundColony stimulating factor 1 receptor (CSF-1R) is a single channel III transmembrane receptor tyrosine kinase (RTK) and plays an important role in immune regulation and the development of various cancer types. The expression of CSF-1R in colon adenocarcinoma (COAD) and its prognostic value remain incompletely understood. Therefore, we aim to explore the prognostic value of CSF-1R in COAD and its relationship with tumor immunity.MethodsCSF-1R expression in a COAD cohort containing 103 patients was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It is possible that these patients received medical Cannabis chemovars that were THC-rich, with very little CBG, indicating the pressing need for precision medicine that uses the proper treatment. Our findings have immediate practical implications; current treatment protocols that are already in combination with medical Cannabis as palliative care can select the CBG-rich chemovars in combination with immune checkpoint blockade therapy, making it more effective, and providing patients with antitumor properties in addition to the palliative ones 52 , 53 .…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that these patients received medical Cannabis chemovars that were THC-rich, with very little CBG, indicating the pressing need for precision medicine that uses the proper treatment. Our findings have immediate practical implications; current treatment protocols that are already in combination with medical Cannabis as palliative care can select the CBG-rich chemovars in combination with immune checkpoint blockade therapy, making it more effective, and providing patients with antitumor properties in addition to the palliative ones 52 , 53 .…”
Section: Discussionmentioning
confidence: 86%
“…In patients with triple-negative breast cancer (TNBC), 35 PADI4 expression correlated with the transcriptional networks known to promote protumor macrophages ( Figure S1D ). In patients with colorectal cancer, 36 DE analysis revealed that PADI4 was among the most highly expressed PTM enzyme in CSF1R high TAMs compared to CSF1R low TAMs ( Figure S1E ). CSF1R high TAMs exhibit a strong immunosuppressive phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…CSF-1R signaling is crucial to macrophage differentiation and survival (79, 80). The density of CSF-1R+ TAMs in tumors correlates with poor outcomes in many tumor types, including colon adenocarcinoma, pancreatic cancer, classical Hodgkin lymphoma, leiomyosarcoma, hepatocellular carcinoma and breast cancer (81)(82)(83)(84)(85)(86). CSF-1R is also expressed by other immune cells within the TME such as DC, MDSCs and neutrophils, and blocking CSF-1R signaling may therefore also deplete these cells in addition to TAMs (87).…”
Section: Colony-stimulating Factor 1 Receptor Blockadementioning
confidence: 99%